(untitled) (Research, Society and Development, 2021)
Autistic Spectrum Disorder (ASD) can be understood with a kind of disorder related to neurodevelopment, characterized by changes in socio-communicative aspects and in behaviors with limited interests. It should be noted that the main language problems present difficulties in semantic, pragmatic, syntactic, paralinguistic, and phonological aspects. The main objective of this research is to analyze the importance of speech therapy interventions in autistic children. Among the specific objectives, the following stand out: Check which difficulties exist in the autistic person in the process of language acquisition; Present speech therapy models and / or strategies with autism; Describe the importance of speech therapy therapeutic intervention programs in the development of autistic communication. To support the research, there was a need for an integrative bibliographic review, analyzing different sources, present in scientific articles, available in the databases of Scielo, Pubmed, Google Acadêmico and Capes. It was evidenced through research that they are effective in the development of the autistic child, enabling a greater benefit in the communicative development of these human beings.